THE ETHICAL THESAURUS AS COMPOUND A THEORETICAL COMPONENT OF A SCHOOL RATE (Pedagogy of Higher and Secondary Education, 2007)
In article separate components in structure of textbooks on ethics for pupils 5-6 classes of general educational high school are characterizedfrom the point of view of a problem of formation of concepts at lessons of ethics.
Keywords: thesaurus; ethical concepts; definition; formation o f concepts at lessons o f ethics